Definition indicators of quality of the confectionery semi-finished product with powder from carrot - Ianchyk, Mariia; Niemirich, Oleksandra; Yanchyk, Olena; Dranenko, Oksana (My University, 2016)
The technology of receiving finishing semi-finished products provides use of a substance that forms the structure and thickeners. In this regard functional and technological properties of the powder from carrots received by cold spray drying (CSD) were studied. It is obvious that introduction of powder leads to emergence in a ready-made product of a peculiar color, aroma and taste. Therefore, the special attention needs to be paid to research of organoleptic properties of powder from carrots. Powder from carrots has the saturated orange color, homogeneous throughout the mass, a pleasant smell with flavor of carrots, without visible inclusions and impurity. Humidity powder is not more than 5%; water absorption coefficient — 2.325 kg/kg; water connecting ability — 6.15%; emulsifying capacity — 1.94 ml/g; ability to hold oil — 0.805 ml/g. At introduction of powders to confectionery masses it is expedient to use powders with a size of particles up to 15 micron and content of this fraction not less than 75...80%. Justification of these parameters is that particles with sizes more than 20... 25 microns are felt organoleptic. Therefore we investigated by a microscopic method dispersion of powder from carrots. In this powder most (namely 82%) represented the fraction of particles to 15 microns. Considering the above-stated data, this powder was used as a substance that forms the structure for production of a confectionery semi-finished product which includes fondant mass , butter, surfactants and powder from carrots. It was investigated physical and chemical indicators of the received semi-finished product. This semi-finished product has a glossy, but not sticky surface; homogeneous plastic consistence; orange color; pleasant flavor and barely perceptible odor of carrots. Moisture is 11,5%. The content of reducing substances is 4,2%. The size of crystals of the main fraction is 10—15 microns. Apparently from the presented data, at addition of powder from carrots, physical and chemical indicators of quality of a confectionery semi-finished product are in admissible limits of values. Thus, it is shown that powder from carrots cold spray drying provides a confectionery semi-finished product with attractive organoleptic properties and corresponding to physical and chemical indicators of quality.
Keywords: plant powders; confectionery semi-finished product; dispersion; substance; рослинні порошки; кондитерський напівфабрикат; дисперсність; ПАР; кафедра експертизи харчових продуктів; кафедра технології ресторанної і аюрведичної продукції